Effect of coiling temperature on the structure and properties of thermo-mechanically rolled S700MC steel - Oktay S.; di Nunzio P.E.; Cesile M.C.; Davut K.; Şeşen M.K. (Journal of Mining and Metallurgy. Section B: Metallurgy)
The boron-free S700MC steel is usually produced by exploiting the properties of a ferrite-bainite mixed microstructure formed by coiling the strips at a temperature of about 450°C, i.e.below the bainite starting temperature. With the aim of further enhancing the mechanical properties of 6 to 10 mm thick strips, industrial tests were carried out at a coiling temperature of 600°C to promote the formation of a structure of ferrite and carbides, which is also acceptable for this type of steel. Unexpectedly, a microstructure composed of ferrite and martensite was obtained. Compared to the ferritic-bainitic grade, the new structure is characterized by a slight decrease of the yield point but by an increase of the ultimate tensile strength by no less than 80 MPa, with a transition from a quasi-discontinuous to a clearly continuous yielding behaviour. Accordingly, the ratio of yield strength to tensile strength decreases from 0.90 to 0.75 and the impact energy decreases by 35 J and 60 J for the two gauge levels, respectively. The mechanical behaviour of the strips coiled at high temperature is explained as a direct consequence of the dual phase structure with a hard phase interspersed in a soft ferrite matrix. The presence of martensite is explained by the so-called incomplete bainite reaction. The partial transformation into ferrite after coiling and the long time required for the coil to cool down stabilize the untransformed austenite due to the carbon enrichment making bainite formation at lower temperatures impossible.